Anomaly in the opacity of the post-reionization intergalactic medium in the Lyα and Lyβ forest - Eilers, Anna-Christina; Hennawi, Joseph F.; Davies, Frederick B.; Oñorbe, Jose (The astrophysical journal, 2019)
We measure the intergalactic medium (IGM) opacity in the Lyα as well as in the Lyβ forest along 19 quasar sightlines between 5.5 ≲ z abs ≲ 6.1, probing the end stages of the reionization epoch. Owing to its lower oscillator strength, the Lyβ transition is sensitive to different gas temperatures and densities than Lyα, providing additional constraints on the ionization and thermal state of the IGM. A comparison of our measurements to different inhomogeneous reionization models, derived from post-processing the Nyx cosmological hydrodynamical simulation to include spatial fluctuations in the ultraviolet background or the gas temperature field, as well as to a uniform reionization model with varying thermal states of the IGM, leads to two primary conclusions: First, we find that including the effects of spectral noise is key for a proper data to model comparison. Noise effectively reduces the sensitivity to high-opacity regions, and thus even stronger spatial inhomogeneities are required to match the observed scatter in the observations than previously inferred. Second, we find that models that come close to reproducing the distribution of Lyα effective optical depths nevertheless underpredict the Lyβ opacity at the same spatial locations. The origin of this disagreement is not entirely clear, but models with an inversion in the temperature-density relation of the IGM just after reionization is completed match our measurements best, although they still do not fully capture the observations at z ≳ 5.8.